INDUCED MATURATION IN THE INDIAN SHORT-FINNED EEL ANGUILLA BICOLOR BICOLOR McCLBLLAND - Dorairaj, K; Kandasami, D; Soundararajan, R (Indian Journal of Fisheries, 2011)
After acdimaitisiag the eels Anguilla bicolor bicolor in sea water, various’ hormones viz., Gonadairaiphon F. S. Hâ€ž Gonadotraphon L. H. and Chorionic Gonadotropin (Profasd) and OcirpHpituiiitiairy extracts were administered to different dosages through intramuscular injections. By mepeated hormone JnjeotiJans maturatiion w:b induced in both tihe sexes. flHr*i*tLallty one imaile eeil which was given 2000 IU of Goaadoliraphon L.H. through four injections, reached spawning oondiiitilon 144 days after the first injection. Mter partial spawning, the eedl died on the same day. The gamadosomiaitic index was 6.47 and eye index increased by 14.38%. Each sperms itozoiid has a comma shaped body and a long ital. One female eel on which was administered 240 mg of camp pituitary extract and 19,000 IU of Chorionic gonadotropin (Profasd) ’hormone (ttorouglh 16 tojeotiians, attained1 ’staiip-irOpe’ condition 98 days after the first injedctfan and yielded 185,6 g of eggs on stripping. The gonadosoiraaitic index was 33.5 The total weight and eye index of the eel increased by 2.9% and 24.1%, respectively. The Mumiber of stripped aggs was estimated to be 0.35 million. The mature eggs were spherical and reJatdvely umlortn in suae measuring 1.00 mm (+ 0.08 mm) in diameter. Attempts made for amtificJJ fentdlisaton wene not successful. Fully developed ovary of A. bicolor bicolor is described1.